Examining the Factors Affecting the Allocation of Financial Resources in Vietnam - Thanh, Le Trung; Khuong, Nguyen Duc (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
This study presents a methodology for measuring the allocation of financial resources and examinines the impact of some factors on the economic development. Based on ​​Wurgle (2000), we expand to establish the coefficient by economic structure and examines the main impact of financial development on the allocative efficiencies from 1995 to 2016 in Vietnam and some neighboring countries. The results from the Autoregressive distribution lag model ARDL show the non-linear relationship follows invertedU-shaped between credit to the private sector and the efficiency of allocation follow the inverted U shape. This supports increasing credit to private sector in order to optimize allocation . In addition, we also provide some shreds of evidence of the impact of external financial resources, the development of the stock market, trade openness, money supply, interest rate spread and government spending affect the efficiency of the allocation financial resources. Keywords Financial resources allocation, financial development, efficiency. References [1] Wurgler, J., “Financial markets and the allocation of capital”, Journal of Financial Economics, 58 (2000), 187-214. [2] Fisman, R., & Love, I., “Financial Development and Growth in the Short and Long Run”, NBER Working Paper Series, 2003. [3] Ahmed, M. H., Lemma, Z., & Endrias, G., “Measuring technical, economic and allocative efficiency of maize production in subsistence farming: Evidence from the central”, Applied studies in Agribusiness and Commerce - APSTRACT, 9 (2015) 3, 63-74. [4] Lala, A., & Kuri, P. K., “Measurement ofAllocative Efficiency in Agriculture and its Determinants: Evidence from Rural WestBengal, India”, International Journal of Agricultural Research, 6 (2011) 5, 377-388. [5] Liu, Z. Y., “An Overview of Financial Resources Allocation in China”, Paper presented at the 2011 International Conference on Financial Management and Economics, Singapore, 2011. [6] Hsieh, C. T., & Klenow, P. J., “Misallocation and manufacturing TFP in China and India”, Quarterly Journal of Economics, 124 (2009) 4, 1403-1448. [7] Whited, T. M., & Zhao, J., “The Misallocation of Finance”, Ross School of Business Paper No. 1295 (2016). [8] Lashitew, A. A., “Misallocation, Aggregate Productivity and Policy Constraints: Cross-country Evidence in Manufacturing”, 2012. [9] Libert, T., “Misallocation and aggregate productivity: Evidence from the French manufacturing sector”, 2016. [10] Ha, D. T. T., Kiyota, K., & Yamanouchi, K., “Misallocation and Productivity: The Case of Vietnamese Manufacturing”, Asian Development Review, 33 (2016) 2, 94-118. [11] Yuan, Y. F., & Cao, X. H., “Empiricalresearchonthenexusoffinanceandgrowthefficiency”, Statistical Research, 24 (2007) 5, 60-66. [12] Zhang, H. B., & Q., X., “The Relationship between Financial Resource Allocation Efficiency and Growth in Different Areas of China”, Paper presented at the The 19th International Conference on Industrial Engineering and Engineering Management, 2012. [13] Zhang, Y. M., Jin, H., & Li, Y. Y., “A Study on the Relationship between Financial ResourceAllocation and Economic Growth Basedon Hebei Province”, 2015 International Conference on Management Science & Engineering (22th), Dubai, UnitedArabEmirates. [14] Ahmad, E., & Malik, A., “Financial sector development and economic growth: An empirical analysis of developing countries”, Journal of Economic Cooperation and Development, 30 (2009) 1, 17-40. [15] Juan, S., Jie, D., & Ping, K., International Journal of Applied Economic Studies, 4 (2016) 4, 1-9. [16] Adu, G., Marbuah, G., & Mensah, J. T., “Financial development and economic growth in Ghana: Does the measure of financial development matter. Review of Development Finance, 3 (2013), 192-203. [17] Bena, J., & Ondko, P., “Financial Development andAllocation of External Finance”, Working Paper Series CERGE-EI, 2009. [18] Fisman, R., & Love, I., “Financial Development and Growth in the Short and Long Run”, NBER Working Paper Series, 2004. [19] Ang, J. B., & Mckibbin, W. J., “Financial liberalization, financial sector development and growth: Evidence from Malaysia”, Brookings Discussion Papers In International Economics, No. 168 (2005). [20] Pesaran, M. H., Shin, Y., & Smith, R. J., “Bounds testing approaches to the analysis of level relationships”, Journal of Applied Econometrics, 16, 3, 289- 326.